A Study of Elamite Kurdish Myths, Stories, and Motifs from Greimasian Perspective - Ali hasan Sohrabnejad; Negar Nuri (پژوهشنامه ادبیات کردی)
Oral literature is a part of folklore that is the legacy of fictional and non-fictional traditions of the past people. has taken. There are many critiques today that are based on structural functions. Structuralists have always sought to find patterns in which to examine stories. Among narrators, Greimas has a particular interest in popular literature, which is applicable to Kurdish motifs. The purpose of this study is to study the myths, stories and Kurdish myths of Ilam based on Greimas theory. Due to the lack of scientific study and the need for a structural study and the great reputation of this theory, an attempt has been made to answer this main question, what is the representation of the study of Elamite myths, tales and motels based on Greimas theory. To answer the questions, 127 motels were selected from 5 books using the library method and then evaluated with the pattern of double confrontations and triple chains of Greimas. The result of this study indicates the existence of six actors in motels. Thirteen groups can be identified in terms of the presence or absence of characters. In some stories, one or more actors are absent, with the sender having the highest frequency in this regard. In the classification of character types, men are the most used and creatures are the least used. Greimas narrative chains are also seen in all motels.